Mothers in Presargonic Ĝirsu - Rauchhaus, Felix (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
This paper aims to make mothers visible — to be precise, mothers from Presargonic Sumer — and contribute to the field of gender studies. Hereby, this study focuses on describing the realities of having been a mother.2 The intention is to understand how mothers from different economic backgrounds performed paid work, undertook unpaid domestic labor, and which responsibilities they shouldered. Additionally, the patriarchal system in Sumer (e.g., Garfinkle 2008; Wright 2008: 260–262; Steinkeller 2013: 350–351) that made mothers financially dependent on their husbands is contrasted with the high financial and social appreciation and prestige mothers could experience on an individual basis.